2011
DOI: 10.1051/0004-6361/200913256
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and excitation of thermal methanol in 6.7 GHz maser bearing star-forming regions

Abstract: Context. Candidate high-mass star-forming regions can be identified through the occurrence of 6.7 GHz methanol masers. In these sources the methanol abundance of the gas must be enhanced, because the masers require a considerable methanol path length. The place and time of origin of this enhancement is not well known. Similarly, it is debated in which of the physical components of the high-mass star-forming region the masers are located. Aims. The aim of this study is to investigate the distribution and excita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…The coverage of the first torsionally excited state also enables to constrain the intensity of the far-infrared radiation field within astrophysical sources. Torsionally excited emission has already been observed in some objects (e.g., Torstensson et al 2011) and will become routine with ALMA.…”
Section: Recent Collision Calculationsmentioning
confidence: 89%
See 1 more Smart Citation
“…The coverage of the first torsionally excited state also enables to constrain the intensity of the far-infrared radiation field within astrophysical sources. Torsionally excited emission has already been observed in some objects (e.g., Torstensson et al 2011) and will become routine with ALMA.…”
Section: Recent Collision Calculationsmentioning
confidence: 89%
“…The advantage of this improved method (sometimes called the 'population diagram') is that it also provides an estimate of the size of the emitting region. An example of combining the two methods is the analysis of CH 3 OH line images of the Cep A region, where classic rotation diagrams work well for the diffuse extended gas, while optical depth correction are needed close to the central protostar (Torstensson et al 2011).…”
Section: Single Excitation Temperature ('Lte') Modelsmentioning
confidence: 99%
“…Such ring-like characteristics were also seen in water masers associated with slightly more advanced stages, where masers were likely tracing an accretion disc or its remnant (Motogi et al 2011a). Torstensson et al (2011b) analysed some of these ring-like maser sources using thermal emission at arcsec scale and found that mostly the distribution of the methanol gas peaks at the maser position with the larger scale gas showing a modest outflow velocity. They argued that the methanol gas has a single origin in these sources, possibly associated with an accretion shock.…”
Section: The Morphology Of 67 Ghz Masersmentioning
confidence: 99%
“…These transitions are not excited in the cloud where mostly low-J transitions emit (E up /k 10 B~K ), and they are only moderately excited in hot cores where emission from higher-J transitions is more dominant (E up / k 100 B  K). The J = 7 K -6 K transitions of methanol around 338 GHz are particularly well suited, both because they are good outflow tracers and because instruments exist to map emission efficiently (e.g., Kristensen et al 2010;Torstensson et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The J=7 K -6 K transitions of methanol around 338 GHz are particularly well suited, both because they are good outflow tracers, and because instruments exist to map emission efficiently (e.g. Kristensen et al 2010, Torstensson et al 2011.…”
Section: Introductionmentioning
confidence: 99%